The politics of security lists. (February 2016) - de Goede, Marieke; Sullivan, Gavin
The authors contributed equally to the paper The List, one of the most archaic means of written enumeration and classification, has made a forceful recurrence in the post-9/11 global security landscape. From terrorist sanctions lists and No-Fly lists to "kill-lists" for drone warfare; from the privately compiled lists of risky banking clients to the regulatory lists of untrustworthy or incompliant companies, the list seems to proliferate as a contemporary technology of security and regulation. How and why are lists becoming newly embedded in security practices? What work do lists perform as specific techniques of government and forms of normative ordering? And what consequences follow for how problems of legal accountability and political responsibility are currently understood and addressed? This paper frames security lists as inscription devices that are heterogeneous, unpredictable and productive in unforeseen ways. It draws attention to the ways they materialise the categories they purport to describe, and how they enact novel forms of knowledge, jurisdiction and targeting. We suggest that critiques could be strengthened by making visible and contesting the fragmented and diffuse conditions through which security lists are produced.